Effect of Long-Term Consumption of Lactobacillus paracasei SD1 on Reducing Mutans streptococci and Caries Risk: A Randomized Placebo-Controlled Trial - Rawee Teanpaisan; Supatcharin Piwat; Sukanya Tianviwat; Benchamat Sophatha; Thanyanan Kampoo (MDPI AG, 2015)
Background: A previous study revealed Lactobacillus paracasei SD1, a probiotic strain, could reduce mutans streptococci (MS). The aim of this study was to evaluate the long-term effects of L. paracasei SD1 on the colonization of MS, and whether caries lesions developed. Methods: After informed consent, 122 children were recruited and randomly assigned to the probiotic or control groups. The probiotic group received milk-powder containing L. paracasei SD1 and the control group received standard milk-powder once daily for six months. Salivary MS and lactobacilli were enumerated using differential culture at baseline and at three-month intervals for 12 months. The persistence of L. paracasei SD1 was investigated using AP-PCR for DNA-fingerprinting. Oral health was examined at baseline and at the end of the study according to WHO criteria. Results: The long-term consumption could prolong colonization of L. paracasei SD1. Significantly reduced MS counts and increased lactobacilli levels were found among children in the probiotic group. There were less caries lesions in the probiotic group at the end of the study. A significant reduction of the development of new caries lesions (4.5 times) was observed in the high caries risk group but not in the low caries risk group. Conclusions: Results demonstrate that the long-term daily ingestion of the human-derived probiotic L. paracasei SD1 significantly reduces the number of MS and caries risk in the high caries group.